(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
The use of online media has now grown rapidly. Online media is not only used as a communication tool but is also used as a medium for promotion or branding. SDN Pandanrejo 02 is one of the schools located in Bumiaji sub-district. This school focuses on realizing a school that cares and has an environmental culture. To create characteristics or "image" that is different from other schools, School Branding is needed. The purpose of this work program activity is to introduce, build, and grow the SDN Pandanrejo 02 brand so that it can be accepted by the wider community. Creating school branding, can be done through several programs that can be developed by the school, one example of which is the "Adiwiyata School Program". The school branding program is running smoothly and it is hoped that with this program, SDN Pandanrejo 02 can have characteristics or an image that is different from other schools. Schools also need to innovate on how to build school branding by using online media and also utilizing technology such as school websites or school social media that can be used to publish various activities, achievements, and testimonials about the school.